The Internalization of Religious Moderation Values Through Islamic Religious Education Learning at SMA Negeri 15 Bandar Lampung - Nisyah Aulia Habibah,; Muhammad Mustofa,; Ida Faridatul Hasanah,; Uswatun Khasanah, (Inspiratif Pendidikan, 2025)
The purpose of this study is to analyze the process of internalizing religious moderation values through Islamic Religious Education (PAI) learning at SMA Negeri 15 Bandar Lampung. This research focuses on teachers’ strategies in instilling religious moderation values, teachers’ exemplary role as agents of moderation, the school’s role as a moderation ecosystem, and students’ responses as indicators of the success of value internalization at school. The research employed a qualitative method with a case study approach. Data collection techniques included observation, interviews, and documentation. The results of the study indicate that PAI teachers play an active role in integrating religious moderation values, such as tolerance, fairness, respect for differences, and love for the homeland into learning materials and methods. Internalization is carried out through teachers’ exemplary behavior, habituation, classroom discussions, and the integration of moderation values in religious extracurricular activities. Positive student responses, such as refraining from mocking one another, respecting individual freedom in practicing their religion, and showing openness during classroom learning by allowing and encouraging peers to express their opinions, demonstrate that the internalization of religious moderation values through PAI learning has been successfully implemented at SMA Negeri 15 Bandar Lampung. This study emphasizes that Islamic Religious Education plays a strategic role in shaping a moderate generation that is tolerant, inclusive, and of strong character, in line with the vision of religious moderation in Indonesia.